A CONTRASTIVE ANALYSIS OF INFLECTIONAL MORPHOLOGY IN THE INDONESIAN AND ENGLISH LANGUAGES - Zainuddin Zainuddin; Moch. Subhan Yahya Subhan (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2026)
: This article examines the comparison of inflectional morphology systems between the Indonesian language and the English language, aiming to identify structural and functional differences in the formation of grammatical meaning in verbs and nouns. The study employs a documentary research method by collecting data from Indonesian and English language corpora. The data are analyzed using a descriptive-comparative approach based on structural morphology theory and language typology. The findings reveal that English has a productive and complex inflectional system in which word forms change obligatorily to indicate tense, person, and number. In contrast, Indonesian is primarily analytic and does not formally employ inflection. Instead, it relies on contextual information, auxiliary words, and other morphological processes such as reduplication to convey similar grammatical meanings. The discussion highlights that these differences reflect the fundamental typological characteristics of both languages. Furthermore, they influence sentence structure, meaning-making strategies, and practical applications in language learning and translation. English speakers must pay close attention to grammatical markers embedded in word forms, whereas Indonesian speakers depend more heavily on syntactic context and lexical cues. These distinctions also create challenges for second-language learners, particularly when transferring grammatical patterns from one language to another. The study concludes by emphasizing the importance of understanding cross-morphological structures in linguistic research as well as in intercultural language applications, especially for improving comparative linguistic analysis, effective language pedagogy, accurate translation practices, and broader cross-cultural communication in multilingual contexts.